Preparing and training for the full spectrum of military challenges insights from the experiences of China, France, the United Kingdom, India, and Israel - Johnson, David E. (David Eugene), 1950- (Rand Corporation monograph series., 2009)
"The difficult and continually evolving operations in Iraq and Afghanistan show the complexities of what is now termed irregular warfare and highlight the need for new approaches to the security challenges with which the United States is now contending and will likely confront in the future. The research reported in this monograph focused on answering a rather straightforward, but thus far largely unanswered, question: What can the U.S. military learn from other militaries about how better to prepare for full-spectrum operations and deployments? To this end, RAND was asked by the OSD for Personnel and Readiness to examine the militaries of China, France, the UK, India, and Israel."--P. xiii.